2018
DOI: 10.2739/kurumemedj.ms652004
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Uncontrolled Trial of the Efficacy and Safety of a Hug with Singing and Rocking for Promotion of Relaxation in Pediatric Patients with Severe Motor and Intellectual Disabilities: Study Protocol

Abstract: The term "children with severe motor and intellectual disabilities (SMID)" is a classification based on the degree of disabilities, but not the name of a disease. Suzuki (1995) indicated the presence of children continuously requiring respiratory care, such as mechanical ventilation, tracheotomy, suction, and oxygen ther

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although previous works have suggested that swaying promotes relaxation and sleep in infants [ 13 ] and affects adult sleep while promoting relaxation effects [ 14 ], only a few studies have investigated the impact of sway stimuli applied by sway beds on children with SMID. However, as reported in previous studies [ 15 , 16 , 17 , 18 ], applying a sway stimulus to children with SMID through the introduction of sway beds in schools, in the context of rehabilitation, or as part of leisure activities may result in a daily relaxation effect on children with SMID. To actually apply such sway bed policies in clinical settings, more detailed studies are needed in the future to examine the effect of the sway stimulus in children.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although previous works have suggested that swaying promotes relaxation and sleep in infants [ 13 ] and affects adult sleep while promoting relaxation effects [ 14 ], only a few studies have investigated the impact of sway stimuli applied by sway beds on children with SMID. However, as reported in previous studies [ 15 , 16 , 17 , 18 ], applying a sway stimulus to children with SMID through the introduction of sway beds in schools, in the context of rehabilitation, or as part of leisure activities may result in a daily relaxation effect on children with SMID. To actually apply such sway bed policies in clinical settings, more detailed studies are needed in the future to examine the effect of the sway stimulus in children.…”
Section: Discussionmentioning
confidence: 79%
“…For example, in children with cerebral palsy, horseback riding has been found to reduce muscle tone [ 15 ] and to correct imbalances in autonomic activity [ 16 ], while whole-body vibration reportedly improves muscle tone, joint range of motion (ROM), and ambulatory function [ 17 ]. For children with SMID, an intervention whereby the children were rocked and sung to while being hugged was confirmed to promote relaxation effectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decade of research shows that music in general, and group singing in particular, can improve physical and mental health as well as wellbeing (Clift et al, 2016). Singing provides some benefit for a range of populations including older adults (Coulton et al, 2015) and can alleviate physical aspects of various conditions such as Parkinson’s Disease (Stegemöller et al, 2017), Chronic Obstructive Pulmonary Disease (Mcnamara et al, 2017), and Dementia (van der Steen et al, 2017), or to help manage broader problems such as trauma (von Lob et al, 2010).…”
Section: Introductionmentioning
confidence: 99%